2015
DOI: 10.1103/physrevb.92.165430
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nonreciprocal bands in magnetized diatomic plasmonic chains

Abstract: We show that non-reciprocal bands can be formed in a magnetized periodic chain of spherical plasmonic particles with two particles per unit cell. Simplified form of symmetry operators in dipole approximations are used to demonstrate explicitly the relation between spectral non-reciprocity and broken spatial-temporal symmetries. Due to hybridization among plasmon modes and free photon modes, strong spectral non-reciprocity appears in region slightly below the lightline, where highly directed guiding of energy c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…By the next nearest neighbor approximation together with quasistatic approximation, the dipole moment p n ; σ ( x component) induced on the nanoparticle σ  =  A or B in the n th unit cell follows the coupled dipole equation20434962:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the next nearest neighbor approximation together with quasistatic approximation, the dipole moment p n ; σ ( x component) induced on the nanoparticle σ  =  A or B in the n th unit cell follows the coupled dipole equation20434962:…”
Section: Methodsmentioning
confidence: 99%
“…The particle array is modeled as an array of point dipole scatters embedded in air for the sake of simplicity. By the next nearest neighbor approximation together with quasistatic approximation, the dipole moment p n;σ (x component) induced on the nanoparticle σ = A or B in the nth unit cell follows the coupled dipole equation 23,33,44,45 :…”
Section: Analytical Evaluation Of Zak Phasementioning
confidence: 99%
“…Metal nanoparticle lattice is a particular type of photonic systems which supports the collective resonance of localized surface plasmons of individual particles and have distinctive band dispersions [50][51][52][53][54][55][56]. Several studies have reported the interesting topological phenomena emerging in this type of system [34,[57][58][59][60]. Specially, 2D honeycomb plasmonic lattices are made up of one-layer-thick metal particles and arranged in a honeycomb structure just like graphene, which can be regarded as a compound structure nested with two triangular sublattices.…”
Section: Honeycomb Plasmonic Lattice and Different Boundariesmentioning
confidence: 99%
“…Metal nanoparticle lattice is a particular type of photonic systems which supports the collective resonance of localized surface plasmons of individual particles and have distinctive band dispersions [50][51][52][53][54][55][56]. Several studies have reported the interesting topological phenomena emerging in this type of systems [34,[57][58][59][60]. Specially, 2D honeycomb plasmonic lattices are made up of one-layer-thick metal particles and arranged in honeycomb structure just like graphene, which can be regarded as a compound structure nested with two triangular sublattices.…”
Section: Honeycomb Plasmonic Lattice and Different Boundariesmentioning
confidence: 99%